40th AIAA Aerospace Sciences Meeting &Amp; Exhibit 2002
DOI: 10.2514/6.2002-569
|View full text |Cite
|
Sign up to set email alerts
|

Noise, turbulence, and thrust of subsonic free jets from lobed nozzles

Abstract: A study of noise benefit, vis-à-vis thrust penalty, and its correlation to turbulence intensities was conducted for free jets issuing from lobed nozzles. Four convergent nozzles with constant exit area were used in the experiments. Three of these were of rectangular lobed configuration having six, ten and fourteen lobes; the fourth was a circular nozzle. Increasing the number of lobes resulted in a progressive reduction in the turbulence intensities as well as in the overall radiated noise. The noise reduction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
14
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 18 publications
2
14
0
Order By: Relevance
“…In fact, the authors observed that the distance of the first peak from the jet exit, scales on the width of the lobes (a1), with 4 ≤ Z/a1 ≤ 6. In our case, the first peak in the CO/P nozzle jet occurred at Z/a1 =5.2, which falls within the reported range [13].…”
Section: Flow Characteristicssupporting
confidence: 71%
See 2 more Smart Citations
“…In fact, the authors observed that the distance of the first peak from the jet exit, scales on the width of the lobes (a1), with 4 ≤ Z/a1 ≤ 6. In our case, the first peak in the CO/P nozzle jet occurred at Z/a1 =5.2, which falls within the reported range [13].…”
Section: Flow Characteristicssupporting
confidence: 71%
“…Whereas the second peak is believed to be related to the wall damping effect [60], the occurrence of the first peak is not fully understood. From the study of Zaman et al [13] on a free rectangular lobed jet, the appearance of a sharp peak on the axial turbulence intensity near the jet exit could be related to the merging of the shear layers shed from an individual lobe. In fact, the authors observed that the distance of the first peak from the jet exit, scales on the width of the lobes (a1), with 4 ≤ Z/a1 ≤ 6.…”
Section: Flow Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…This relatively slow speed case was selected in order to avoid any significant compressibility effects. Comparison of PIV data from this Mach 0.5 jet case with hot-wire measurements from a Mach 0.3 round jet investigated in reference [12] indicated very similar normalized mean flow and turbulence statistics, which verifies that the current Mach 0.5 case under consideration will not be noticeably biased by compressibility effects. In addition to the baseline Chien k-model and the modified k-model using the Var-D correction, we also examine the Menter Shear-Stress Transport (SST) model (Refs.…”
Section: Evaluation Of Var-d Correction For Jet Sp#3mentioning
confidence: 73%
“…It is to be noted that, since the sixties, much before the findings of Liepmann and Gharib (Liepmann, 1991;Liepmann and Gharib, 1992) on the important part played by the streamwise structures in mixing, artificial streamwise vorticity generation methods are used in aeronautics and combustion in order to improve mixing (Kuchar and Chamberlin, 1980;Paterson, 1984;Presz et al, 1986Presz et al, , 1994Presz et al, and 2002Zaman, et al, 1994;Zaman, 1996aZaman, , 1996bZaman, , 1999Zaman, and 2003Ramesh et al, 2006). The currently used passive generators of streamwise vortices are small tabs or chevrons placed at the nozzle exit.…”
Section: Introductionmentioning
confidence: 99%